Analisis Getaran Whole Body pada Supir Angkutan Umum di Samarinda - Puspa Syadariah; Devina Rayzy Perwitasari Sutaji Putri; Pratiwi Sri Wardani; Mislan Mislan; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Whole body vibration is vibration that propagates throughout the worker's body from vibration sources in the form of machines, vehicles, and so on. In this paper it is reported the results of research to determine the total value of vibration acceleration on several drivers of the public transport in Samarinda and to analyze the comfort level of the drivers receiving the vibration on their bodies. The components of the vibration acceleration were measured by using a vibration meter type of Svantex 106. The comfort level of the driver in receiving the vibration was assosiated with the scale of comfortable level set by the Ministry of Manpower of the Republic of Indonesia by decree number PER.13/MEN/X/2011. The research found that the average of the total value of vibration acceleration received by the drivers in A, B, and C transportations were 0.3877 m/s2 , 0.7056 m/s2 dan 0.6596 m/s2 , respectively. In Samarinda the drivers in B and C transportations were more uncomfortable to receive the whole body vibration than the drivers in C transportation.